2018
DOI: 10.3802/jgo.2018.29.e70
|View full text |Cite
|
Sign up to set email alerts
|

Negative peritoneal washing cytology during interval debulking surgery predicts overall survival after neoadjuvant chemotherapy for ovarian cancer

Abstract: ObjectiveOptimal debulking in interval debulking surgery (IDS) after neoadjuvant chemotherapy (NAC) has been reported as a prognostic factor for patients with ovarian cancer. However, the identification of microscopic residual disease (MRD) using visualization and palpation is subjective. Peritoneal washing cytology (PWC) during IDS is an easy-to-implement, objective approach for assessing disease status, although its clinical relevance and association with MRD is not known. The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(32 reference statements)
0
3
3
Order By: Relevance
“…This careful examination contributed to increased detection rate of positive‐PWC in this study. Compared to the positive‐PWC rate in patients with R0 status (28%‐39%) reported by previous studies, this study showed a PWC‐positive rate of 59%.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This careful examination contributed to increased detection rate of positive‐PWC in this study. Compared to the positive‐PWC rate in patients with R0 status (28%‐39%) reported by previous studies, this study showed a PWC‐positive rate of 59%.…”
Section: Discussioncontrasting
confidence: 79%
“…This careful examination contributed to increased detection rate of positive-PWC in this study. Compared to the positive-PWC rate in patients with R0 status (28%-39%) reported by previous studies, 14,15 this study showed a PWCpositive rate of 59%. Using PWC, it was possible to identify those with microscopic residual disease and reduced PFS; therefore, more intensive therapy or a chemotherapy regimen different from neoadjuvant chemotherapy may be considered for improving clinical outcomes.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In this study, we retrospectively analyzed data from 25 patients with advanced ovarian cancer who underwent NAC/IDS at our institution, and we investigated the prognostic signi cance of PWC in NACtreated patients. While previous studies have highlighted the improved prognosis with NAC/IDS and the importance of optimal debulking [1,2,11], our ndings deviate from previous reports [5,6,12] by indicating no signi cant differences in OS and PFS between patients with positive and negative PWC, regardless of RD status. One possible explanation for this difference is the incorporation of adjuvant therapy post-IDS, including BEV or PARPi, which may have improved outcomes by suppressing malignant cell growth and peritoneal metastasis [7,13].…”
Section: Discussioncontrasting
confidence: 99%
“…This system has shown to correlate with progression-free [10, 11] and overall survival [12]. Clinical studies have shown that negative PC specimens collected at IDS are associated with an increased overall survival [13]. Similar cytologic characterization of post NACT specimens has not been performed.…”
Section: Introductionmentioning
confidence: 99%